A bump in the road: speed bumps' impact on property values. Issue 1 (4th February 2019) - Graham, John Edward; Jones, Adam Talbot
Abstract : Purpose: Speed bumps invite varied responses from homeowners, drivers and policymakers. Parents of small children like speed bumps, if they slow the passing traffic, but prospective home buyers may reject a home with a speed bump nearby, contemplating the traversal of it thousand times during an ownership period. The purpose of this study is to empirically identify the effect of speed bumps on home values. Design/methodology/approach: Analysis presented here is based on an examination of home sales prices and exploits variation in the number of speed bumps traversed and the installation of speed bumps to identify the effect of speed bumps on home values. An anonymous online survey is also used to shed light on drivers of the empirical results. Findings: Initial results exploiting variation in the number of bumps traversed suggest speed bumps are associated with reduced residential property values. An estimated treatment effect of speed bump installation underscores the original findings. Finally, survey results imply that older homeowners and homeowners with children may favor speed bumps but less than the disfavor of those who do not. Research limitations/implications: The research presented here applies to speed bumps in residential areas and on streets not considered through streets. Practical implications: The findings suggest that planners should investigate options such as medians and roundabouts instead of speed bumps. Social implications: These results suggest that communities can be visually improved and home values lifted through the removal of speed bumps and installation of other traffic control devices. Originality/value: This research is valuable to residential developers, planners and neighborhood associations across the country.